Investigating the molecular aetiology of Obsessive-compulsive disorder (OCD) and clinically-defined subsets of OCD - Hemmings, Sian M. J. (Stellenbosch : Stellenbosch University, 2006)
Thesis (PhD (Psychiatry))-- Stellenbosch University, 2006.